Forensic mental health service implications of COVID-19 infection in Nigeria - A. Ogunwale (Forensic Science International: Mind and Law, 2020)
Forensic mental health services are fledgling in most African countries including Nigeria. The current formulation of such services in Nigeria is correctional psychiatry in addition to some hospital-based services. The COVID-19 pandemic presents significant challenges to the already fragile state of forensic mental health services within the country. Its impact includes limitation of access to and continuity of mental healthcare in prison as well as reduction in referrals from other services within the criminal justice system such as the police and the courts. Further tapering of previously less prominent aspects of forensic mental health service in the country such as the preparation of psychiatric court reports has also been observed. Forensic psychiatry training and research have equally been hampered by the pandemic. The lessons learnt from these challenges should offer practitioners and policy makers insight into strategic developmental objectives for the post-COVID era within services and training programmes.